2011
DOI: 10.1200/jco.2011.29.18_suppl.lba5006
|View full text |Cite
|
Sign up to set email alerts
|

Result of interim analysis of overall survival in the GCIG ICON7 phase III randomized trial of bevacizumab in women with newly diagnosed ovarian cancer.

Abstract: LBA5006 Background: ICON7 was designed to investigate safety and efficacy of adding bevacizumab to standard chemotherapy in women with newly diagnosed ovarian cancer. Analyses of mature progression-free survival (PFS) data suggest a PFS benefit from bevacizumab (p=0.0041, a 15% improvement at 12 months and 1.5 months overall), and a trend for overall survival (OS) improvement, hazard ratio (HR)=0.81, 95%CI=0.63 to 1.04, p =0.098. The final analysis of OS will be performed when 715 deaths have occurred. An int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Overall, two studies 14 , 15 contained multiple comparisons among different experimental therapies and a common control arm. There were twotrials 15 , 16 of biological therapies and another two trials 17 , 18 of intraperitoneal therapy. In total, seven comparisons reported an improvement in PFS (upper limit of the 95% CI for HR <1.00 or reported p < 0.05) and four comparisons reported an improvement in OS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, two studies 14 , 15 contained multiple comparisons among different experimental therapies and a common control arm. There were twotrials 15 , 16 of biological therapies and another two trials 17 , 18 of intraperitoneal therapy. In total, seven comparisons reported an improvement in PFS (upper limit of the 95% CI for HR <1.00 or reported p < 0.05) and four comparisons reported an improvement in OS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the majority of patients relapse and the addition of a third cytotoxic drug, such as gemcitabine, topotecan, caelyx or epirubicin, to platinum and paclitaxel has yielded disappointing results 9193 . The VEGF-binding antibody bevacizumab has been added in Phase III trials (Gynecologic Oncology Group 218 study (GOG218; clinical trial ID: NCT00262847) and ICON7 (NCT00483782)) to standard treatment during and up to 15 months after chemotherapy, with reports of improved progression-free survival 94,95 , as well as increased overall survival in high-risk subgroups (patients with stage IV disease or suboptimally debulked stage III disease) 96 . Randomized trials have indicated that bevacizumab, concurrent with and following chemotherapy, can also provide benefit in terms of delaying further recurrence in both platinum-sensitive (OCEANS trial (NCT00434642) 97 ) and platinum-resistant (AURELIA trial (NCT00976911) 98 ) disease.…”
Section: The Treatment Of Ascitesmentioning
confidence: 99%
“…ICON7, however, additionally included women from stage I, II, or III following debulking and stage IV patients. ICON7 followed a different dosage schedule (7.5 mg/kg) every three weeks versus GOG-218, which administered double the dose at 15 mg/kg every three weeks 8,9. In addition to concluding the same results as GOG-218 with regard to PFS, ICON7 also revealed an improved OS to those patients deemed to have poor prognosis or high-risk disease (stage IV disease, inoperable stage III, or suboptimally debulked stage III disease).…”
Section: Anti-angiogenesismentioning
confidence: 99%